Evaluation of different polishing agents on root surface topography of human extracted teeth - Priya Kaushal; Mukesh Kumar; Rajan Gupta; Parveen Dahiya; Vrishti Bansal; Sunita R Melwani (Wolters Kluwer Medknow Publications, 2019)
Context: Polishing is an important step in oral prophylaxis procedure, which retards further accumulation of plaque on the root surface. Aim: The present in vitro study was to evaluate the efficacy of Sodium Bicarbonate Prophy Powder and Glycine Prophy Powder to produce minimum roughness on the root surface of cementum and dentin. Methods: Forty-five samples were collected and stored in saline. Scaling and root planing of each sample were done. Each sample was mounted on acrylic block so as to leave one surface of the root exposed. A tentative area on the proximal side of root 4 mm apically from cementoenamel junction was demarcated. Forty-five specimens were randomly divided into three groups - Group 1: Control group, Group 2: Polished with Sodium Bicarbonate Prophy Powder, and Group 3: Polished with Glycine Prophy Powder. All the samples were analyzed under surface roughness tester, and average roughness values were calculated. Statistical Analysis Used: The values obtained were statistically analyzed using the NPAR test. Results: The study revealed that average roughness is significantly less after using Glycine Prophy Powder than Sodium Bicarbonate Prophy Powder. Conclusion: Glycine Prophy Powder is a more efficient polishing powder in producing less roughness on the root surface as compared to Sodium Bicarbonate Prophy Powder.